2017
DOI: 10.1159/000479482
|View full text |Cite
|
Sign up to set email alerts
|

Increased Retinal Thinning after Combination of Internal Limiting Membrane Peeling and Silicone Oil Endotamponade in Proliferative Diabetic Retinopathy

Abstract: Background: The aim of this study was to examine the change in retinal thickness after vitrectomy with internal limiting membrane (ILM) peeling and/or silicone oil (SO) endotamponade in proliferative diabetic retinopathy (PDR). Methods: The actual amount and ratio of changes in the retinal thickness were calculated. Results: Compared to control eyes in the ILM peeling (-)/SO (-) group, the central, superior inner, and temporal inner retina in the ILM peeling (+)/SO (-) group, the central and superior inner ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 37 publications
0
11
1
Order By: Relevance
“…Interestingly, the retinal thicknesses in eyes with PVR undergoing SO endotamponade were thinner than those in healthy eyes, but they were thicker in eyes with PDR and RD undergoing SO endotamponade. We previously reported, in cases with PDR undergoing SO endotamponade, the retinal thickness decreased after SO evacuation 8. In this study, however, we found that the retinal thickness increased in eyes with PDR that were filled with SO.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Interestingly, the retinal thicknesses in eyes with PVR undergoing SO endotamponade were thinner than those in healthy eyes, but they were thicker in eyes with PDR and RD undergoing SO endotamponade. We previously reported, in cases with PDR undergoing SO endotamponade, the retinal thickness decreased after SO evacuation 8. In this study, however, we found that the retinal thickness increased in eyes with PDR that were filled with SO.…”
Section: Discussioncontrasting
confidence: 76%
“…We measured retinal thicknesses (average retinal thickness within 1000-μm diameters centered from the fovea and 4 sectors around the fovea) according to the early treatment diabetic retinopathy study (ETDRS) chart,8 1 month after the first vitrectomy surgery and just before the SO evacuation surgery. We analyzed possible associations between the retinal thickness changes and SOF cytokine levels.…”
Section: Methodsmentioning
confidence: 99%
“…The findings from the present study showed that the risk of increased IOP was significantly increased with the use of silicone oil endotamponade but there was no significant difference between the patients with silicone oil endotamponade diagnosed with retinal detachment compared other indications. Recently, vitreoretinal surgery, including the treatment of retinal detachment, have increasingly used gas endotamponade [29,30]. In our department, SF6 has been increasingly used, but silicone oil endotamponade is used in the increasing numbers of cases of retinal detachment with concurrent proliferative diabetic retinopathy [30].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, vitreoretinal surgery, including the treatment of retinal detachment, have increasingly used gas endotamponade [29,30]. In our department, SF6 has been increasingly used, but silicone oil endotamponade is used in the increasing numbers of cases of retinal detachment with concurrent proliferative diabetic retinopathy [30]. The findings from the present study have shown that to evaluate the significance of the risk of developing raised IOP in patients with retinal detachment with endotamponade other than silicone oil, a larger study group is needed, with a multicenter approach.…”
Section: Discussionmentioning
confidence: 99%
“…The Nagoya University Hospital Ethics Review Board approved this retrospective analysis of patients' data and waived the requirement for informed consent. We measured average retinal thicknesses using the Early Treatment Diabetic Retinopathy Study (ETDRS) chart 31,32 before and 1 and 12 months after the initiation of anti-VEGF treatment.…”
Section: Methodsmentioning
confidence: 99%